2016
DOI: 10.1021/acsami.6b00773
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol-Assisted CVD-Grown PdO Nanoparticle-Decorated Tungsten Oxide Nanoneedles Extremely Sensitive and Selective to Hydrogen

Abstract: We report for the first time the successful synthesis of palladium (Pd) nanoparticle (NP)-decorated tungsten trioxide (WO3) nanoneedles (NNs) via a two-step aerosol-assisted chemical vapor deposition approach. Morphological, structural, and elemental composition analysis revealed that a Pd(acac)2 precursor was very suitable to decorate WO3 NNs with uniform and well-dispersed PdO NPs. Gas-sensing results revealed that decoration with PdO NPs led to an ultrasensitive and selective hydrogen (H2) gas sensor (senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 44 publications
6
55
0
Order By: Relevance
“…5,27,[33][34][35] It is worth noting that the formation of p-n heterojunctions is an efficient and cost-effective technique to improve the activity and sensitivity of gas sensors 3,34,35 , and hierarchical structures offer abundant pores and large surface area which benefit the diffusion and adsorption of testing gases. 26 For example, Deng et al 16 prepared CuO-TiO2 heterostructure nanofibers and found that the formation of p-n heterojunctions considerably improved the sensitivity of TiO2 nanofibers to formaldehyde at 200 ºC.…”
Section: Introductionmentioning
confidence: 99%
“…5,27,[33][34][35] It is worth noting that the formation of p-n heterojunctions is an efficient and cost-effective technique to improve the activity and sensitivity of gas sensors 3,34,35 , and hierarchical structures offer abundant pores and large surface area which benefit the diffusion and adsorption of testing gases. 26 For example, Deng et al 16 prepared CuO-TiO2 heterostructure nanofibers and found that the formation of p-n heterojunctions considerably improved the sensitivity of TiO2 nanofibers to formaldehyde at 200 ºC.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of oxygen species depends on the temperature of the metal oxide [19,22,23]. O 2(g) ↔ O 2(ads) O 2(ads) + e − ↔ O 2 − (ads)    (<150 °C) O 2 − (ads) + e − ↔ 2O − (ads)    (150–400 °C) O − (ads) + e − ↔ O 2− (ads)    (>400 °C)…”
Section: Discussionmentioning
confidence: 99%
“…Pt or Pd nanoparticles supported onto n-type metal oxides have been reported to enhance response towards hydrogen via a combination of chemical and electronic sensitization effects [19,22,23]. …”
Section: Discussionmentioning
confidence: 99%
“…Pt-nanoparticle decorated WO3 nanowires were co-deposited directly onto the electrode area in a single step aerosol assisted-CVD (AA-CVD). Prior to the deposition of the nanowires, the substrate was heated to a temperature of 380 °C, and followed by the transfer of ultrafine aerosols to the heated substrate by N2 carrier gas at a flow rate of 0.5 L/min [5,7]. Surface morphology images were taken using Scanning Electron Microscopy (ESEM) with FEI Quanta 60 and Tunneling Electron Microscopy with JOEL model 1011 equipment.…”
Section: Methodsmentioning
confidence: 99%
“…To this end, there has been much progress in the fabrication, and integration of different single crystalline SMOx nanostructures decorated with metal nanoparticles for gas sensing at low temperature; as well as optimizing the minimum power consumption of such devices while maintaining high sensor performance and stability [4]. Recently, highly sensitive gas sensors based on nanoparticle decorated WO3 nanowires for the detection of various gases at low temperature have been explored [5,6].…”
Section: Introductionmentioning
confidence: 99%